2000
DOI: 10.1590/s0066-782x2000000900001
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory blood pressure monitoring and microalbuminuria in normotensive subjects with insulin-dependent diabetes mellitus

Abstract: Objective -To assess the association between microalbuminuria with ambulatory blood pressure monitoring in normotensive individuals with insulin-dependent diabetes mellitus. Methods -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
0
7
0
3
Order By: Relevance
“…These findings suggest that crude increases in ambulatory nighttime BP compared to the nondipping phenomenon are more relevant in identifying diabetic patients at increased risk of microvascular complications [63]. Similar microalbuminuria-oriented findings were endorsed in adult [68] and pediatric [69] type 1 diabetic patients, further confirming the comparative predominance of absolute nighttime BP over circadian BP variability [70,71]. By contrast, the superiority of nondipping status over nighttime BP on microalbuminuria can be supported only by two small studies – the first recruiting 79 normotensive subjects and the latter 29 children with chronic renal failure [72,73].…”
Section: Introductionmentioning
confidence: 62%
“…These findings suggest that crude increases in ambulatory nighttime BP compared to the nondipping phenomenon are more relevant in identifying diabetic patients at increased risk of microvascular complications [63]. Similar microalbuminuria-oriented findings were endorsed in adult [68] and pediatric [69] type 1 diabetic patients, further confirming the comparative predominance of absolute nighttime BP over circadian BP variability [70,71]. By contrast, the superiority of nondipping status over nighttime BP on microalbuminuria can be supported only by two small studies – the first recruiting 79 normotensive subjects and the latter 29 children with chronic renal failure [72,73].…”
Section: Introductionmentioning
confidence: 62%
“…There was no statistical difference in systolic, diastolic, and mean nondippers between microalbuminuric and normoalbuminuric patients. Cohen et al [13] observed a lower but an insignificant decline of nighttime BP in micro-normoalbuminuric patients.…”
Section: Discussionmentioning
confidence: 94%
“…Lurbe et al [4] revealed that an increase in blood pressure during sleep, detected by ambulatory blood pressure monitoring, preceded the development of microalbuminuria and stated that an early increase in nighttime arterial blood pressure may have a key role in the development of diabetic nephropathy. Cohen et al [13] showed higher mean pressure values during day and nighttime in microalbuminuric diabetic adults. In adolescents any elevation of albumin excretion even above the upper limit of normal is associated with higher prevalence of elevated BP levels, and elevation of diastolic BP more than 22% is a greater risk of albuminuria [12].…”
Section: Discussionmentioning
confidence: 94%
“…The existence of an association between greater pressure loads and increased UAE was demonstrated in patients with DM Type 1 44,45 and Type 2 13 . Recently, correlations between pressure loads and UAE, left ventricular mass, interventricular thickness, and left posterior ventricular wall in Type 2 DM patients 41 were demonstrated by our group.…”
Section: Pressure Loads and Diabetes Mellitusmentioning
confidence: 91%
“…Most studies that analyzed this ABPM parameter focused on the development and progression of DN. Some authors found positive results 35,40,[52][53][54][55][56] , while others were not able to establish this relationship 44,57,58 . Most studies were carried out crosssectionally or with cases and controls, merely suggesting an association between the factor under study (nocturnal BP fall) and the outcome (DN), and some presented statistical analysis and data interpretation susceptible to criticism 54,55 .…”
Section: Masked Hypertension (%)mentioning
confidence: 96%